Odpowiedzi

2010-03-22T01:56:02+01:00
1
a)
W(x)=x³-4x²=x²(x-4)
W(x)=0 dla x=0 lub x=4
b)
W(x)=x³+2x²=x²(x+2)
W(x)=0 dla x=0 lub x=-2
c
W(x)=x³-9x=x(x²-9)=x(x-3)(x+3
W(x)=0 dla x=0 lub x=3 lub x=-3
d
W(x)=x³-x=x(x²-1)=x(x-1)(x+1)
W(x)=0 dla x=0 lub x=1 lub x=-1
e
W(x)=2x³+6x²=2x²(x+3)
W(x)=0 dla x=0 lub x=-3
f
W(x)=-x³+3x=-x(x²-3)=-x(x-√3)(x+√3)
W(x)=0 dla x=0 lub x=√3 lub x=-√3

2
-x(x-5)(x-1/3)(x+1/3)(x-7)(x-3)=0
Δ=100-84=16
√Δ=4
x=7
x=3

x=0 ∨x=5∨x=1/3∨x=-1/3∨x=7∨x=3
b
2x²(2-x)5(x-3)(x+3)4(x-1/4)(x+3)=0
Δ=121+48=169
√Δ=13
x=-3
x=1/4
x=0∨x=2∨x=3∨x=-3∨x=1/4

c
(x-1)(x²+x+1)(x-3/4)(x+3/4)3(x-5)(x+2/3)=0
Δ=169+120=289
√Δ=17
x=5
x=-2/3
x=1∨x=3/4∨x=-3/4∨x=5∨x=-2/3

d
[6x(x+2)+1(x+2)](x²-2x+4)(3x-1)²=0
((x+2)(6x+x²-2x+4)(3x-1)²=0
(x+2)(x²+4x+4)(3x-1)²=0
(x+2)(x+2)²(3x-1)²=0
x=-2∨x=-1/3
e
x²(3x-1)-7(3x-1)=0
(x²-7)(3x-1)=0
(x-√7)(x+√7)(3x-1)=0
x=√7∨x=-√7∨x=1/3
f
x²(2x+5)-2(2x+5)=0
(x²-2)(2x+5)=0
(x-√2)(x+√2)(2x+5)=0
x=√2∨x=-√2∨x=-2,5
g
(x²+6)(x+2)=(x²+6)(x-√6)(x+√6)
(x²+6)(x+2)-(x²+6)(x-√6)(x+√6)=0
[(x²+6)(x+2-(x-√6)(x+√6)=0
[(x²+6)(x+2-x²+6)=0
[(x²+6)(x-x²+8)=0
Δ=33
x=(-1-√33)/2
x=(-1+√33)/2

h
(x²+6)(x+2)=(x²-6)(x²+6)
(x²+6)(x+2)-(x²-6)(x²+6)=0
(x²+6)[x+2-(x²-6)]=0
(x²+6)[x+2-x²+6)]=0
(x²+6)[x+-x²+8)]=0
Δ=33
x=(-1-√33)/2
x=(-1+√33)/2

zad3
tgα=3/4
tgα=4/x
4/x=3/4
x=24/3
x=8
6²+8²=c²
c²=36+64
c²=100
c=10